India in the Indo-Pacific: Strategic Autonomy and Opportunities for the European Union and Spain. - García García, Andrea (Journal of the Spanish Institute for Strategic Studies, 2026)
This article analyses India’s role in shaping the Indo-Pacific and its implications for the European Union and Spain. Building on the legacy of non-alignment and the evolution towards strategic autonomy, it examines the main doctrines guiding Indian foreign policy, such as the Act East Policy, the SAGAR initiative, and The India Way. The study explores the pillars of India’s strategic projection: economic growth, military modernisation, and connectivity projects, particularly the India–Middle East–Europe Economic Corridor. It also addresses the rivalry with China, cooperation with the United States within the Quad, and opportunities for partnership with the EU in trade, technology, and maritime security. Special attention is given to the implications for Spain, highlighting the 2024 Joint Declaration and industrial and logistical cooperation. The article concludes that India is emerging as an indispensable partner for Europe’s strategic diversification and as an opportunity for Spain to strengthen its international profile in defence, energy, and connectivity.
Keywords: India; Indo-Pacific; Strategic autonomy; European Union; Spain